A genetic variant in SLC6A20 is associated with Type 2 diabetes in white‐European and Chinese populations. Issue 11 (12th August 2014) - Ling, Y.; van Herpt, T. T. W.; van Hoek, M.; Dehghan, A.; Hofman, A.; Uitterlinden, A. G.; Jiang, S.; Lieverse, A. G.; Bravenboer, B.; Lu, D.; van Duijn, C. M.; Gao, X.; et al.
Abstract Aims To investigate whether polymorphisms in SLC6A20 are associated with susceptibility to Type 2 diabetes. Methods In the Rotterdam Study, a prospective, population‐based cohort (n = 5974), 22 tagging polymorphisms with minor allele frequencies>0.05 across SLC6A20 were studied. Replication studies were performed in an independent Dutch case–control study (DiaGene‐Rotterdam Study 2 n = 3133), and in a Chinese Han case–control population (n = 2279). A meta‐analysis of the results was performed. Results In the Rotterdam study, the minor alleles of rs13062383, rs10461016 and rs2286489 increased the risk of Type 2 diabetes (hazard ratio 1.37, 95% CI 1.15–1.63, hazard ratio 1.30 95% CI 1.09–1.54 and hazard ratio 1.20, 95% CI 1.07–1.35, respectively). In the DiaGene/Rotterdam Study 2, the A allele of rs13062383 increased the risk of Type 2 diabetes (odds ratio 1.45, 95% CI 1.19–1.76). In the Chinese Han study, the rs13062383 A allele also increased the risk of Type 2 diabetes (odds ratio 1.21, 95% CI 1.03–1.42). Meta‐analysis showed a highly significant association of rs13062383 with Type 2 diabetes (odds ratio 1.35, 95% CI 1.21–1.47; P = 3.3 × 10‐8). Conclusions In conclusion, rs13062383 in SLC6A20 increased the susceptibility to Type 2 diabetes in populations with different genetic backgrounds.